2007
DOI: 10.1194/jlr.m700154-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

De novo biosynthesis of the late endosome lipid, bis(monoacylglycero)phosphate

Abstract: Bis(monoacylglycero)phosphate (BMP) is a unique lipid enriched in the late endosomes participating in the trafficking of lipids and proteins through this organelle. The de novo biosynthesis of BMP has not been clearly demonstrated. We investigated whether phosphatidylglycerol (PG) and cardiolipin (CL) could serve as precursors of de novo BMP synthesis using two different cellular models: CHO cells deficient in phosphatidylglycerophosphate (PGP) synthase, the enzyme responsible for the first step of PG synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 69 publications
(94 reference statements)
1
69
0
Order By: Relevance
“…we observed that increasing the synthesis of PG by phosphatidylglycerophosphate synthase overexpression was not associated with an enhanced formation of CL in CHO cells (29). Consistently, we did not measure any accumulation of CL after supplementation with 18:1/18:1-PG or 22:6/22:6-PG, confirming the absence of a tight correlation between PG and CL.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…we observed that increasing the synthesis of PG by phosphatidylglycerophosphate synthase overexpression was not associated with an enhanced formation of CL in CHO cells (29). Consistently, we did not measure any accumulation of CL after supplementation with 18:1/18:1-PG or 22:6/22:6-PG, confirming the absence of a tight correlation between PG and CL.…”
Section: Discussionsupporting
confidence: 71%
“…Numerous studies have clearly established that exogenous PG and cardiolipin (CL) could serve as precursors for BMP synthesis (25)(26)(27)(28). Recently, we have reported that PG, but not CL, is an endogenous precursor of BMP (29). Of interest, Waite et al (27) have pointed out some variability in the level of BMP synthesis with PG derived from different PL precursors, which they proposed to be related to differences in PG FA composition.…”
mentioning
confidence: 99%
“…Indeed, it has been shown that two polyglycerophospholipids, phosphatidylglycerol (PG), a structural isomer of LBPA and cardiolipin, can be converted to LBPA in in vivo systems (Poorthuis and Hostetler 1975;Somerharju and Renkonen 1980;Amidon et al 1995). However, it was also shown that only PG, but not cardiolipin, serves as a possible precursor for de novo LBPA biosynthesis in vivo (Hullin-Matsuda et al 2007). Strikingly these studies also show that despite decreased de novo LBPA synthesis in cells deficient for PG synthesis, the total LBPA amount remains unchanged, indicating that some other biosynthetic pathway must exist.…”
Section: Restricted Lipid Localization Via Spatially Controlled Synthmentioning
confidence: 60%
“…BMP is thought to be derived from PG since cells deficient in PG synthesis have reduced ability to produce this lipid (31). Remarkably, BMP was reported to date only in eukaryotes, with a strict endosome /lysosomes distribution, and it is still largely unknown how BMP is produced and transported to endo-lysosomes.…”
Section: Bmpmentioning
confidence: 99%